2006
DOI: 10.1128/aem.72.1.353-360.2006
|View full text |Cite
|
Sign up to set email alerts
|

A Bacillus thuringiensis S-Layer Protein Involved in Toxicity against Epilachna varivestis (Coleoptera: Coccinellidae)

Abstract: The use of Bacillus thuringiensis as a biopesticide is a viable alternative for insect control since the insecticidal Cry proteins produced by these bacteria are highly specific; harmless to humans, vertebrates, and plants; and completely biodegradable. In addition to Cry proteins, B. thuringiensis produces a number of extracellular compounds, including S-layer proteins (SLP), that contribute to virulence. The S layer is an ordered structure representing a proteinaceous paracrystalline array which completely c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
42
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 25 publications
2
42
0
Order By: Relevance
“…The finding that BslK also contains a NEAT domain prompted an investigation into whether this potential surface protein partakes in heme binding and transfer. Treatment of B. anthracis cells expressing a His-tagged form of BslK with guanidine led to the release of BslK H6 into the supernatant, a finding consistent with the extraction of noncovalently associated S-layer proteins from the bacterial surface as reported by others (32,42,53,63,70). Immunofluorescence microscopy using Texas Red-conjugated anti-hexahistidyl antibodies also indicated that BslK H6 localized to the bacterial surface (Y. Tarlovsky and A. W. Maresso, unpublished observations).…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…The finding that BslK also contains a NEAT domain prompted an investigation into whether this potential surface protein partakes in heme binding and transfer. Treatment of B. anthracis cells expressing a His-tagged form of BslK with guanidine led to the release of BslK H6 into the supernatant, a finding consistent with the extraction of noncovalently associated S-layer proteins from the bacterial surface as reported by others (32,42,53,63,70). Immunofluorescence microscopy using Texas Red-conjugated anti-hexahistidyl antibodies also indicated that BslK H6 localized to the bacterial surface (Y. Tarlovsky and A. W. Maresso, unpublished observations).…”
Section: Discussionsupporting
confidence: 58%
“…To determine if cell-associated BslK H6 is a surface protein, we treated BslK H6 -expressing cells with guanidine-HCl (GN), a chaotropic agent known to induce the release of noncovalently attached cell envelope proteins such as S-layer polypeptides from the surface of bacteria (42,63,70). B. anthracis cells were grown in the presence of IPTG, and bacterial sediments were treated with 4 M guanidine for 5 min.…”
Section: Resultsmentioning
confidence: 99%
“…Cell adhesion is the major role of SLPs. An S-layer protein coming from B. thuringiensis GP1 strains has also been reported to have high insecticidal activity against the coleopteran pest Epilachna varivestis (38). In the present article, except for the SLPs that may play roles in cell integrity and shape maintenance or cell adhesion, we identified an S-layer protein, EA1 (Q63FB8), which belongs to B. cereus.…”
Section: Discussionmentioning
confidence: 76%
“…3,4) S-layers play key roles in the interaction between bacterial cells and environment as protective coats, structures involved in cell adhesion and surface recognition, molecular sieves, attachment structures for high-molecular-mass extracellular proteins such as amylases, and in the sorption of toxic heavy metal ions. [5][6][7] Furthermore, it has been indicated that the S-layer might act as a virulence factor in several pathogenic bacteria, such as the S-layer protein produced by Bacillus thuringiensis GP1, which shows insecticidal activity against the coleopteran Epilachna varivestis, 8) and the S-layer of Lactobacillus acidophilus which mediates the adherence of the strains to avian intestinal epithelial cells. 9) B. sphaericus is a naturally occurring gram-positive soil bacterium that represents a strictly aerobic group of mesophilic endospore-forming bacteria.…”
mentioning
confidence: 99%